Elementary School Students Pirls Evaluation System For Independent Reading Teaching In A Hand-Held Tool - Olimjonova Oʻgʻilxon Abdurasul qizi (Zien Journals, 2024)
This article talks about the methods, their types, methods of conducting, etc., aimed at attracting primary school students to independent study and preparing them for the PIRLS international assessment program
Keywords: PIRLS; international program; skills; analysis